Management and Concept of Functional Literacy Program in India: Addressing Functional Illiteracy in India: A Comprehensive Analysis and Recommendations (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the present existence, in India, there are number of individuals who are unable to read and write, there is lack of awareness amongst them, they are residing in the conditions of poverty and backwardness, they do not have employment opportunities, they are unable to sustain their living conditions and, in some cases get involved in social problems, such as, criminal and violent acts. These are hindrances within the course of social life development. Therefore, to alleviate these problems and in making provision of assistance to them to enhance their living conditions, it is important to recognize the mass program of functional literacy. The main areas that have been taken into account in this research paper are, functional literacy, National Adult Education Program, National Literacy Mission, Saakshar Bharat Mission, Functional Literacy for Adult Women, Farmer’s Functional Literacy Project, Rural Functional Literacy Program, analysis of the materials and the media software used in the functional literacy programs and recommendations.